The Effect of Process Innovation, Product Innovation, and Technology on Operational Performance at PT Pagilaran UP Pagilaran Batang, Central Java - Rahma - Ulfa; Dody - Setyadi; M - Nahar (Admisi dan Bisnis, 2021)
This study aims to find out the influence variables of process innovation, product innovation, and technology for operational performance at PT Pagilaran UP Pagilaran. The data analysis technique used multiple regression as technique analysis. The data collection methode in this study used are observation, questionnaires, and documentation. From this analysis it can be concluded that process innovation, product innovation, and technology have a positive effect on operational performance. The results of the t-test and f-test in this study indicate that process innovation, product innovation, and technology have a significant effect on operational performance. Furthermore, based on the results of the descriptive analysis of process innovation, product innovation, technology, and operational performance, the criteria for a high index value mean that the variables have been carried out well by PT Pagilaran UP Pagilaran Batang